Agglomeration, urbanization and competitive performance: the natural experiment of English football. Issue 1 (1st January 2019) - Jones, Calvin; Jordan, Declan
ABSTRACT: There are sound theoretical and empirical bases for expecting productivity and innovative benefits for businesses located in large urban areas, and for those located closer to others in the same or related industries. However, the size and precise origin of these effects remain uncertain and complicated by potential endogeneity from businesses' location choice. English football is proposed as a natural experiment with immobile businesses and evidence is presented from the English Premier League (EPL) that suggests urban scale affects clubs' relative performance. It is found that teams in larger conurbations perform relatively better, and it is suggested these benefits probably originate from the sport's novel labour market.